2017
DOI: 10.3390/socsci6040114
|View full text |Cite
|
Sign up to set email alerts
|

‘You Will Have These Ones!’: Six Women’s Experiences of Being Pressured to Make a Contraceptive Choice That Did Not Feel Right

Abstract: This study aims to contribute to an understanding of women's experiences of contraceptive counselling, and of being pressured to make a contraceptive choice that did not feel right. Six women in Sweden participated in semi-structured interviews, which were analysed through interpretative phenomenological analysis. The results were organised into three themes: (1) The normalisation process, i.e., the ways in which the women experienced using the contraceptive were being promoted as a natural part of womanhood; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Morison et al [ 33 ] note that expert-directed decision-making in contraceptive care, in which patient knowledge or concerns are not considered, may lead to covert patient resistance through discontinuation of contraceptive use. Poor PCC in contraceptive care can also damage the patient-provider relationship [ 34 , 104 , 105 ] and increase distrust in healthcare [ 26 , 106 ]. In other contexts too, such as among patients with contested diseases [ 107 ], distrust in medicine and withdrawal from care-seeking have been related to experiences of feeling deprioritized or badly treated by caregivers [ 6 , 39 , 40 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Morison et al [ 33 ] note that expert-directed decision-making in contraceptive care, in which patient knowledge or concerns are not considered, may lead to covert patient resistance through discontinuation of contraceptive use. Poor PCC in contraceptive care can also damage the patient-provider relationship [ 34 , 104 , 105 ] and increase distrust in healthcare [ 26 , 106 ]. In other contexts too, such as among patients with contested diseases [ 107 ], distrust in medicine and withdrawal from care-seeking have been related to experiences of feeling deprioritized or badly treated by caregivers [ 6 , 39 , 40 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Worth noting here, firstly, is that limitations in PCC [79] have been observed in research on contraceptive care, where caregivers have been noted to downplay, dismiss or neglect to discuss (concerns about) potential side effects of contraceptives including copper IUDs [24,[26][27][28][29][30][31][32][33]35]. In a study of contraceptive care in Sweden [34], some women reported having felt patronized and bereft of agency, as their worries were dismissed and their experiences invalidated by caregivers. The researchers observed that due to the existing provider/patient power hierarchy, the affirmation of differing views or actions demanded strong self-efficacy on the part of the patient (cf [109]).…”
Section: Identifying Limitations In and Developing Pccmentioning
confidence: 99%
See 3 more Smart Citations